(untitled) (Research, Society and Development, 2025)
This study aimed to propose a practical guide for the personalized prescription of compounded probiotics and prebiotics, based on scientific evidence, by relating specific strains, pathologies, and effective dosages. A narrative review with an integrative approach was conducted, with a literature search in scientific databases (PubMed, Scopus, Embase) and technical documents from reference institutions (WHO, FAO, EFSA), covering the period from 2010 to 2025. Randomized clinical trials, systematic reviews, and technical consensus documents were included. A total of 24 probiotic strains and 6 prebiotics with documented clinical use were selected. Data were organized into a summary table correlating specific pathologies with recommended symbiotics (probiotics + prebiotics) and their effective dosages (Shart 1). Key findings include: Lactobacillus plantarum and Bifidobacterium infantis for gastrointestinal diseases; B. lactis and L. gasseri in metabolic syndromes; L. helveticus and B. breve in emotional disorders; P. freudenreichii in inflammatory conditions; L. crispatus for gynecological health; and B. breve and E. faecium in pediatrics. Dosages ranged from 1×10⁸ to 1×10¹⁰ CFU/day, depending on the clinical condition and strain. Personalized and compounded symbiotic prescriptions, grounded in the correlation between pathology, strain, and dosage, represent a promising approach in integrative medicine, contributing to safer, more effective, and evidence-based clinical interventions.